The death of strategic plan: questioning the role of strategic plan in self-initiated projects relying on stakeholder collaboration - Tiwari, Reena; Winters, J. (Routledge, 2016)
This paper is an outcome of the authors’ involvement in a community development and capacity building project which commenced in 2010 in a small village in North India. Using a collaborative and participatory approach, the specific nature of this project influenced the development of objectives, the planning process, role planning and role allocation for different participants, and the subsequent actions. No structured strategic plan had previously been developed, nor was one constructed at the initial stages of this project. The lack of a strategic plan did not impact negatively on the project outcomes. This paper questions the need and value of the traditional strategic plan for projects requiring the participation throughout the multiple stakeholders. The paper asks: Has the strategic plan lost its relevance in today’s changed planning context?